An ImmunoPEGliposome for Targeted Antimalarial Combination Therapy at the Nanoscale - Arnau Biosca; Lorin Dirscherl; Ernest Moles; Santiago Imperial; Xavier Fernàndez-Busquets (MDPI AG, 2019)
Combination therapies, where two drugs acting through different mechanisms are administered simultaneously, are one of the most efficient approaches currently used to treat malaria infections. However, the different pharmacokinetic profiles often exhibited by the combined drugs tend to decrease treatment efficacy as the compounds are usually eliminated from the circulation at different rates. To circumvent this obstacle, we have engineered an immunoliposomal nanovector encapsulating hydrophilic and lipophilic compounds in its lumen and lipid bilayer, respectively. The antimalarial domiphen bromide has been encapsulated in the liposome membrane with good efficiency, although its high IC50 of ca. 1 µM for living parasites complicates its use as immunoliposomal therapy due to erythrocyte agglutination. The conjugation of antibodies against glycophorin A targeted the nanocarriers to Plasmodium-infected red blood cells and to gametocytes, the sole malaria parasite stage responsible for the transmission from the human to the mosquito vector. The antimalarials pyronaridine and atovaquone, which block the development of gametocytes, have been co-encapsulated in glycophorin A-targeted immunoliposomes. The co-immunoliposomized drugs have activities significantly higher than their free forms when tested in in vitro Plasmodium falciparum cultures: Pyronaridine and atovaquone concentrations that, when encapsulated in immunoliposomes, resulted in a 50% inhibition of parasite growth had no effect on the viability of the pathogen when used as free drugs.